Strengthening Small-Scale Snakehead (Channa Striata) Aquaculture through the Implementation of the IoT-Based “Channa Sense” Monitoring System - Latifah Husni Nyayu; Muslim Muslim; Rusman Ariyanto; Ade Silvia Handayani; Umul Salamah; Muhammad Ardiansyah; Rita Martini; Rusman Ariyanto; Ekawati Prihatini; Cinda Anugrah Citra (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2026)
Small-scale snakehead (Channa striata) farmers commonly rely on manual and periodic water quality monitoring, which often results in delayed responses to environmental fluctuations and high fry mortality rates. This community service program aimed to strengthen technological literacy and improve hatchery management practices through the implementation of an Internet of Things (IoT)-based “Channa Sense” real-time monitoring system. The intervention adopted a structured three-phase approach consisting of pre-implementation assessment, participatory workshop and system installation, and post-implementation evaluation. The program involved 37 participants representing farmers, entrepreneurs, and community members, with baseline data collected from 30 small-scale farmers across Palembang, Indralaya, and Musi Banyuasin. Pre-intervention findings showed that 56.76% of participants were unaware of the technology and none had prior experience with digital monitoring systems. Following experiential learning activities, 64.86% of participants reported a moderate to full understanding of the system, and recognition of Channa Sense as a water quality monitoring device increased from 13.51% to 60.42%. At the partner hatchery (Kandang Om Bobby), real-time monitoring reduced fry mortality from approximately 40% to 5–10%, representing a survival improvement of 30–35%. The findings indicate that participatory and context-adapted IoT interventions can effectively bridge digital literacy gaps while generating measurable operational benefits in small-scale aquaculture. However, adoption intentions remained moderate due to cost and maintenance concerns. Continued mentoring, cost optimization, and cooperative-based implementation strategies are recommended to ensure long-term sustainability and broader community uptake